Texas Phoenix Palm Decline - Nigel A. Harrison; Monica L. Elliott (EDIS)
Texas Pheonix palm decline is a new disease in Florida, caused by an unculturable bacterium. It is a fatal, systemic disease that kills palms relatively quickly. This revised 6-page fact sheet explains the pathogen and hosts of TPPD, its symptoms, how to diagnose it, and provides disease management practices. Written by Nigel A. Harrison and Monica L. Elliott, and published by the Plant Pathology Department, June 2016.